1997
DOI: 10.1111/j.1348-0421.1997.tb01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Lambda‐Toxin of Clostridium perfringens Activates the Precursor of Epsilon‐Toxin by Releasing Its N‐ and C‐Terminal Peptides

Abstract: Abstract:The effect of ă-toxin, a thermolysin-like metalloprotease of Clostridium perfringens, on the inac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
151
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 39 publications
(15 reference statements)
2
151
1
3
Order By: Relevance
“…ETX is the third most lethal of all clostridial toxins, ranking behind only the Clostridium botulinum and Clostridium tetani neurotoxins [4]. The fact that the 50% lethal dose (LD 50 ) of ETX in mice is 50 ng·kg −1 [5] underpins the potential to use this toxin as a bioterrorist weapon; therefore, ETX is regarded as a potential bioterrorism agent by the US Government Centers for Disease Control and Prevention [3]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETX is the third most lethal of all clostridial toxins, ranking behind only the Clostridium botulinum and Clostridium tetani neurotoxins [4]. The fact that the 50% lethal dose (LD 50 ) of ETX in mice is 50 ng·kg −1 [5] underpins the potential to use this toxin as a bioterrorist weapon; therefore, ETX is regarded as a potential bioterrorism agent by the US Government Centers for Disease Control and Prevention [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The relatively inactive secreted prototoxin is converted to the fully active mature toxin by proteases of the host, such as trypsin and chymotrypsin [6], or by the C. perfringens λ-protease [5]. Active ETX binds to the intestinal epithelium to induce epithelial permeability in the absence of overt histologic damage [7] and enters the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of ε-toxin is the activation of the inactive precursor (ε-protoxin) by proteases such as trypsin, chymotrypsin (Hunter et al, 1992), and λ-protease produced by C. perfringens. This activation is accompanied by removal of both N-and C-terminal peptides (Jin, et al 1996;Minami et al, 1997).…”
Section: Epsilon-toxin (ε ε ε ε ε)mentioning
confidence: 99%
“…This toxin accumulates mainly in the brain and kidneys when intravenously injected into rats (14), causing injury to neuronal cells (15)(16)(17) and cerebral blood vessels (18). One characteristic feature of the toxin is its extraordinarily high potency; 20 ng of ET kills a mouse within 1 h. 2 We have previously shown that proteolytic activation of ⑀-protoxin (ProET) is due to the removal of a C-terminal peptide (19,20) and that activated ET forms a heptamer in rat synaptosomal membranes (20). Similar ET oligomerization has been reported for Madin-Darby canine kidney (MDCK) cell membranes, where the potassium ion permeability is increased by the toxin (21).…”
mentioning
confidence: 99%